Cognitive Predictors of Success in Computer Programmer Training - Jacobs, Stuart J. (ACM, 1973)
The aptitudes and abilities required for the position of programmer, within the computer industry, have yet to be fully studied and their inter-relationships known. Although the industry is relatively new, a substantial amount of research in the areas of personnel selection, evaluation and job requirements has been undertaken. Yet these studies have confined themselves primarily to the use of interest scales, aptitude and achievement tests as overall predictors for on-the-job success rather than in the study of the cognitive factors pertinent to the tasks of which programming is composed. In a study by Deutsch and Shea, Inc. (1963), the relationship between the programmer and the computer is seen as analogous to that of the mahout and his elephant. As with the mahout, the programmer uses his intelligence, skills and abilities in the control and guidance of a powerful and flexible, yet non-intelligent, tool in the performance of specific finite operations which contribute to the completion of more complex tasks. It is the programmer who, when presented with a problem from science, engineering or business, must work out a solution. John and Miller (1957) state that all problems have two general parts: the specific components involved (i.e., data, etc.) and the relationships which are the orderings of or changes to the specific components.
Keywords: dept.csc